Can private school growth foster universal literacy? Panel evidence from Indian districts - Sarmistha Pal; Geeta Gandhi Kingdon (Institute for the Study of Labor (IZA), 2010)
Millennium Development Goals (MDGs) set the agenda for the attainment of universal literacy by 2015 primarily to be delivered by the state sector. This agenda tends to ignore the significant private school growth around the world since early 1990s, thus initiating the policy debate as to whether private school growth may foster 'education for all'. Despite growing literature on the difficulties of attaining MDGs, there is hardly any attempt to assess the role of private sector in this respect. Using India as an important case in point, we intend to bridge this gap of the literature. Results using a unique district-level panel data-set from 17 major states of India for the period 1992-2002 that we compile highlight a significant positive impact of private school growth on literacy while its effect on gender gap in literacy remains rather limited in our sample. Compared to 15-19 year olds, private school effect of literacy is stronger among 10-14 year old children. Interesting variations across the regions and also among the marginalised ethnic groups are noted. The paper offers explanations for the findings.
Keywords: I21; I28; O15; 330; private school growth; universal literacy; gender gap; Millennium Development Goals; India; Asia